People are the message? Social mobilization and social media in Brazil - Cardoso, G.; Lapa, T.; Di Fátima, B. (International Journal of Communication, 2016)
In June 2013, protesters took to the streets of hundreds of Brazilian cities. The mobilizing factor was the rising fares of public transportation, which precipitated a wave of discontentment characterized by a mix of demands for better public services and changes in the discredited democratic institutions. This article discusses the role of social media in the protests and how such use configures a paradigmatic example of how communication occurs in network societies. To frame the discussion, we examine social media appropriation for the purposes of political participation through a survey applied online in 17 countries and an in-depth analysis of protests in Brazil. Looking at the Brazilian protests, the ways in which the appropriation of social media occurred and institutional responses to demonstrations developed, we argue that in the network society, the people, and no longer the media, are the message.